The strategic role of education for sustainable development. - Matarrita Baccá, Rosaura (2011)
A paradigm shift for developmentthe country, forcing the university, as an institution, to rethink every race so that professionals get a profile form that allows them to respond to the needs of society by integratingaspects related to the conservation and protection of biodiversity, including humans; related organization that maximizes social welfare and live fairly asresponsible, compassionate and aware that the actionsindividual have an impact on society. To achieve this, not only must revamped academic offerings, it is necessary to have the staff that is infoster conditions that change with seriousness, responsibility and commitment.